Hunting unicorns? Experimental evidence on predatory pricing policies - Aaron S. Edlin; Catherine Roux; Armin Schmutzler; Christian Thöni (University of Zurich, Department of Economics, 2017)
We study the anticompetitive effects of predatory pricing and the efficacy of three policy responses. In a series of experiments where an incumbent and a potential entrant interact, we compare prices, market structures and welfare. Under a laissez-faire regime, the threat of post-entry price cuts discourages entry, and allows incumbents to charge monopoly prices. Current U.S. policy (Brooke Group) does not help. A policy suggested by Baumol (1979) lowers post-exit prices, while Edlin's (2002) proposal reduces pre-entry prices and encourages entry. While both policies show outcomes after entry that are less competitive than under Laissez-Faire, they nevertheless increase consumer welfare.
Keywords: D21; K21; L12; L13; C91; 330; Predatory pricing; entry deterrence; firm strategy; antitrust law; experiment